2021
DOI: 10.3390/antiox10091400
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Hypoxia-Hyperoxia and Oxidative Stress in Developing Human Airway Smooth Muscle

Abstract: Premature infants are frequently and intermittently administered supplemental oxygen during hypoxic episodes, resulting in cycles of intermittent hypoxia and hyperoxia. The relatively hypoxic in utero environment is important for lung development while hyperoxia during the neonatal period is recognized as detrimental towards the development of diseases such as bronchopulmonary dysplasia and bronchial asthma. Understanding early mechanisms that link hypoxic, hyperoxic, and intermittent hypoxic-hyperoxic exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 89 publications
(99 reference statements)
0
5
0
Order By: Relevance
“…Oxidative stress can be triggered by any imbalance in oxygen levels relative to the local tissue's normal state, such as poorly functional, chaotically organized vasculature (often seen in vessel overgrowth), or from changes in oxygen supply (antenatal air exposure or oxygen therapy). 27 The changes in peroxiredoxin expression observed here suggest a deeper change in oxidative stress and warrant further investigation into oxidation of tear proteins themselves or other markers of ROP.…”
Section: Discussionmentioning
confidence: 74%
“…Oxidative stress can be triggered by any imbalance in oxygen levels relative to the local tissue's normal state, such as poorly functional, chaotically organized vasculature (often seen in vessel overgrowth), or from changes in oxygen supply (antenatal air exposure or oxygen therapy). 27 The changes in peroxiredoxin expression observed here suggest a deeper change in oxidative stress and warrant further investigation into oxidation of tear proteins themselves or other markers of ROP.…”
Section: Discussionmentioning
confidence: 74%
“…For example, preconditioning using hyperthermia ( Nosaka et al, 2007 ), ischemia ( Franz et al, 2018 ), or light exercise ( Nausheen et al, 2017 ) have been shown to reduce RE-induced muscle damage and inflammation. In a previous cell culture study, intermittent hypoxia–hyperoxia treatment elevated oxidative stress production in human airway smooth muscle cells ( Bartman et al, 2021 ). Chronic intermittent hypoxia–hyperoxia also increased oxidative damage in lung tissue of neonatal rodents ( Dylag et al, 2017 ; Mohamed et al, 2020 ).…”
Section: Discussionmentioning
confidence: 94%
“…However, episodes of hypoxia or respiratory distress requiring supplemental oxygen, and the subsequent exposure to it, may confer risk of wheezing in the first few years of life. Recent studies in newborn mouse and primary human airway smooth muscle cells suggest intermittent hyperoxia and hypoxia has a long‐term detrimental effect on airway function that may involve oxidative stress 17,18 . Again, this remains an area of interest for future prospective studies to better define the role of oxidative stress, coupled with a potentially immature respiratory system in this patient population.…”
Section: Discussionmentioning
confidence: 99%